The Adaptation of the Teacher’s Sense of Efficacy Scale (TSES-Indonesia): Designed for Gifted Students Educators - Eltri Oktaviola; Fitriani Yustikasari Lubis (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
Teacher efficacy (TE) has been proven to have significant correlation to a teacher’s performance in educating. Despite that significance, there are only a few TE scales available in Bahasa Indonesia, especially ones that are related to gifted students. This research is conducted to adapt Tschannen-Moran and Hoy’s (2001) Teacher’s Sense of Efficacy Scale (TSES) based on the adaptation guideline of International Test Commission ITC (2016). TSES contains three factors which includes student engagement, instructional strategies, and classroom management. Participants of this research amounts to 127 teachers who have previously or is currently teaching gifted students that are obtained through convenient and snowball sampling. Aiken’s V is used to evaluate the scale’s content validity. Evidence of construct validity is gathered through CTT, EFA and CFA analysis. The result of Aiken’s V is considered of high value, which means each item shows relevancy in measuring the construct. With a Cronbach’s Alpha value of 0,908, p-value of >0,05 from the CFA analysis, and CFI, TLI, NFI, IFI, RMSEA, SRMR and CR values that are in accordance with the criteria set. It can be concluded that the TSES-Indonesia (12 items) is proven to be valid and reliable.